2020
DOI: 10.1021/acs.joc.0c01716
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Resolution, Configurational Stability, and Properties of Cationic Functionalized [5]Helicenes

Abstract: A straightforward approach to the synthesis of two different series of cationic [5]helicenes has been achieved including, in dioxa series, the possibility to introduce aromatic functional groups at the periphery of the helical structure. While photophysical study highlights that the introduction of aryl substituents at position 23 of the helical moieties has a negligible impact on the optical properties, styryl substituents allow a welcoming extension of the conjugation pathways. Finally, a redshift of the opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…It was earlier shown that monoaza[5]helicenes rapidly racemize at room temperature and that racemization barriers are lower than for the corresponding carbon analogues [13] . Furthermore, the position of the nitrogen significantly impacts the configurational stability [14] and relatively low barriers were observed for the racemization of cationic diaza[5]helicenes [15] . We thus examined the racemization of the synthesized compound 1 after separation by HPLC on a chiral stationary phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was earlier shown that monoaza[5]helicenes rapidly racemize at room temperature and that racemization barriers are lower than for the corresponding carbon analogues [13] . Furthermore, the position of the nitrogen significantly impacts the configurational stability [14] and relatively low barriers were observed for the racemization of cationic diaza[5]helicenes [15] . We thus examined the racemization of the synthesized compound 1 after separation by HPLC on a chiral stationary phase.…”
Section: Resultsmentioning
confidence: 99%
“…[13] Furthermore, the position of the nitrogen significantly impacts the configurational stability [14] and relatively low barriers were observed for the racemization of cationic diaza [5] helicenes. [15] We thus examined the racemization of the synthesized compound 1 after separation by HPLC on a chiral stationary phase. A sample of enantioenriched 1 in acetonitrile was heated to 40 °C and the racemization was monitored by HPLC (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The brominated product 33b can be further reacted under Suzuki-Miyaura and Sonogashira conditions to yield the diphenyl (36) and diphenylethynyl (37) derivatives (Scheme 29). A very recent paper [57] shows the preparation of a cationic Br-substituted diaza [5] Intermediate 38 can be prepared on a multigram scale and can also be used for the preparation of structurally similar dioxa-and azaoxa-helicenes. It is also possible to prepare the related compounds 39 and 40 (Figure 6) through the transformation of dioxaderivatives.…”
Section: Azahelicenes With Cationic Frameworkmentioning
confidence: 99%
“…However, the relatively low racemization energy barrier of A7H makes it difficult to maintain its chiral configuration at high temperatures during the chemical derivatization or the thermal processing for device fabrication, thus limiting the applications of A7H-based chiral materials. Herein, we report the synthesis and characterizations of a new tetramethyl-substituted aza [7]helicene (TMA7H) by introducing methyl groups at the terminal of the A7H backbone to increase the racemization energy barrier [49][50][51][52][53][54] (Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%